Satellite monitoring of post-mining rehabilitation and the quantification of backfill dynamics using differential SAR interferometry - Haupt, Shelley Adelaide (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.